Enrichments of post‐translational modifications in proteomic studies. Issue 1 (6th November 2019) - Pieroni, Luisa; Iavarone, Federica; Olianas, Alessandra; Greco, Viviana; Desiderio, Claudia; Martelli, Claudia; Manconi, Barbara; Sanna, Maria Teresa; Messana, Irene; Castagnola, Massimo; Cabras, Tiziana
Abstract: More than 300 different protein post‐translational modifications are currently known, but only a few have been extensively investigated because modified proteoforms are commonly present in sub‐stoichiometry amount. For this reason, improvement of specific enrichment techniques is particularly useful for the proteomic characterization of post‐translationally modified proteins. Enrichment proteomic strategies could help the researcher in the challenging issue to decipher the complex molecular cross‐talk existing between the different factors influencing the cellular pathways. In this review the state of art of the platforms applied for the enrichment of specific and most common post‐translational modifications, such as glycosylation and glycation, phosphorylation, sulfation, redox modifications (i.e. sulfydration and nitrosylation), methylation, acetylation, and ubiquitinylation, are described. Enrichments strategies applied to characterize less studied post‐translational modifications are also briefly discussed.